Analisa Perbandingan Anggaran Biaya Pembangunan Kantor Urusan Agama Kecamatan Lingga Bayu dengan Menggunakan Metode SNI 2008 dan AHSP 2016 - Pulungan, Ahmad Hidayat; Yusrizal Lubis, Yusrizal Lubis (Universitas Quality, 2024)
Accurate budgeting is required for each estimator before carrying out a particular project using a clear, economical and standardized method in order to obtain maximum profits. Controlling and planning all resources used in project work such as time, services, labor and materials is very dependent on cost budgeting. This must really be calculated carefully by the estimators so that in the future they do not experience losses and problems after winning the auction. Budgeting for project work financing in Indonesia can usually be done through several types of methods, for example AHSP 2016, SNI 2008, and Burgelijike Openbare Werken (BOW). Even though there are many methods to choose from, experienced contractors generally have their own estimates and analysis techniques based on their experience. However, here the researcher intends to estimate the costs required to build the District Religious Affairs Office. Lingga Bayu and compared which method was the most economical between the 2008 SNI method and 2016 AHSP. The results stated that the budgeting results from both methods were IDR. 1,181,800,000 for SNI 2008 and Rp. 1,077,200,000 for AHSP 2016. On this basis, the most economical method is the AHSP 2016 method.